Un programme technologique basé sur l’analyse de l’activité réelle des enseignants débutants au travail et en vidéoformation - Simon Flandin; Luc Ria (Activités)
This article proposes an approach to the research-design of an educational device related to a logic of teacher professionalization, namely a logic of reasoning on and for the action (Barbier, 2006): the “NéoPass@ction” video platform. Beyond the technical aspects, the total device, which is supported by a hybrid program of research and engineering training, and which is described here on the basis of several complementary works: a) in situ analysis and modelling of the actual work of beginning teachers, b) the design of innovative resources documented through recorded interviews and testimonies and textual explanations and c) assessment of these resources and of the educational devices integrating them, for feedback purposes. These works are analysed using a ternary approach to training devices (Albero, 2010a). The first section describes the initial design process of the device, from ideational foundations (empirically and historically situated theoretical and ethical assumptions about teacher training) to a functional device of reference (explicit operational project, embodied by an online video platform). The second section describes the process of continued design: from the analysis of the lived device, on the users’ side, taking studies conducted in different educational contexts, we identify ways in which beginning teachers use NéoPass@ction and transform their relationship with work. In conclusion, we suggest possible improvements to the platform, along with supports for its use.